2016
DOI: 10.1515/macvetrev-2016-0081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Meat Type, Sex and Storage Time on Fatty Acid Profile of Free Range Dalmatian Turkey

Abstract: Macedonian Veterinary ReviewDalmatian turkey is a slow growing breed kept in free range systems. It is a type of "old fashioned poultry" whose meat is present on the market and accepted by consumers. However, no information about its meat quality and fatty acid profile is available. The chemical composition of the meat was influenced by gender and meat type and these differences could be important from the consumer's point of view. Fatty acid composition was characterized by the predominance of n6 fatty acids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The values found are slightly higher than those reported by Moussa et al (2014) for salmon and sardines, but lower than those reported for tuna and mackerel except for the latter's IT value, which is considerably low (0.17). But when compared to values in turkey meat (Mauric et al, 2016) or in pig fat and muscle (Grela et al, 2014), the ones we found are within the limits of 0.30-0.50 for AI and 0.75-1.2 IT referred by the mentioned authors. When compared with the values reported by Franco et al (2020) for fermented sausages in which the pig fat was partially replaced by linseed oil oleogels, the values in the present work are slightly higher than 0.26-0.39 for AI or 0.28-0.70 for TI.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The values found are slightly higher than those reported by Moussa et al (2014) for salmon and sardines, but lower than those reported for tuna and mackerel except for the latter's IT value, which is considerably low (0.17). But when compared to values in turkey meat (Mauric et al, 2016) or in pig fat and muscle (Grela et al, 2014), the ones we found are within the limits of 0.30-0.50 for AI and 0.75-1.2 IT referred by the mentioned authors. When compared with the values reported by Franco et al (2020) for fermented sausages in which the pig fat was partially replaced by linseed oil oleogels, the values in the present work are slightly higher than 0.26-0.39 for AI or 0.28-0.70 for TI.…”
Section: Resultssupporting
confidence: 83%
“…(2014) for salmon and sardines, but lower than those reported for tuna and mackerel except for the latter's IT value, which is considerably low (0.17). But when compared to values in turkey meat ( Mauric et al., 2016 ) or in pig fat and muscle ( Grela et al., 2014 ), the ones we found are within the limits of 0.30–0.50 for AI and 0.75–1.2 IT referred by the mentioned authors. When compared with the values reported by Franco et al.…”
Section: Resultssupporting
confidence: 77%
“…We observed an acceptable level of AI and TI in meat stored under cooling conditions for 21 days. Literature reports indicate that polyunsaturated fatty acids decrease with storage time (under freezing conditions), worsening AI and TI [ 36 , 37 ]. Although fatty acid profiles of rabbit meat have been studied, little has been done to determine how storage and use affect the PUFA/SFA and AI and TI ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by Mauric et al (2016) indicated that in breast meat of Dalmatian turkeys the content of Saturated Fatty Acids (SFA), MUFA and PUFA were 38.04, 34.62 and 26.54% of total fatty acids. A slight difference was observed in thigh meat: SFA 39.98%, MUFA 33.68% and PUFA 25.77%.…”
Section: Resultsmentioning
confidence: 99%